Notary's Responsibility to the Bank Regarding the Cooperation Agreement for Completion of Mortgage - Lisa Putri Utami; Ariawan Gunadi (Journal of Law, Politic and Humanities, 2024)
Unfulfilled obligations by the Notary in completing the preparation of the Deed of Credit Agreement, Power of Attorney to Enforce Mortgage Rights (SKMHT), Deed of Granting Mortgage Rights (APHT), and Deed of Acknowledgment of Debt in a cooperation agreement with the Bank will cause losses from the Bank. Completion of Deed Making that is not in accordance with the time limit set in the cooperation agreement must be accountable by the Notary to the Bank. The purpose of this research is to find the responsibility of the Notary towards the delay in making the deed and find the legal implications of the delay in making the deed stated in the cooperation agreement. Normative juridical is the type of research used in this research. The result of the research is that the Notary's delay in making the deed in the cooperation agreement with the Bank can be accounted for by the Notary by compensating the losses arising from the Bank and the legal implications when the Notary is late in making the deed can be sued before the court.